A brief overview of Bible translation in South Africa - Hermanson, E. A. (Acta Theologica, 2002)
Christianity came to South Africa in 1652, but missionary outreach to the indigenous population only began in earnest in the 19th century. The first formal-equivalent Bible translations were done by missionaries in the latter part of the 19th and early 20th century. Since the mid-1960s the Bible Society has facilitated functional-equivalent translations by teams of mother-tongue translators, and is currently completing the Old Testament in Southern Ndebele, the only South African official language without a complete Bible. Advances in translation theory present new challenges in translating the Bible to communicate in the contemporary linguistic situation.